Distribution of vehicle speeds in traffic flow on multilane roads approaching major and metropolitan cities - Oksana Hulchak; Stanislav Popov; Liudmyla Nahrebelna; Alina Korchevska (Transport Technologies, 2025)
The distribution characteristics of vehicle speeds on multilane highways approaching major and metropolitan cities, using a six-lane segment of the M-05 Kyiv – Odesa highway as a case study, are investigated in this paper. The research methodology is based on field observations employing frame-by-frame video analysis with an accuracy of 0.04 seconds, enabling precise identification of time headways between vehicles and calculating their instantaneous speeds. Both theoretical and empirical speed distribution curves were constructed. Typical speed ranges for different traffic lanes were identified, and the conformity of the observed data to the normal distribution law was statistically verified.